An equivalent-stepped-index-coupled DFB semiconductor laser and laser array realized by stepping the duty cycle of the Sampled Bragg grating. (April 2015) - Zheng, Junshou; Zhang, Yunshan; Li, Lianyan; Tang, Song; Sh, Yuechun; Chen, Xiangfei
Abstract: An equivalent-stepped-index-coupled (ESIC) distributed feedback semiconductor laser with an equivalent-stepped duty cycle (ESDC) is proposed and investigated numerically. The ESDC grating profile is realized by stepping the duty cycle of a Sampled Bragg grating (SBG) with the uniform seeding grating. Numerical results show that the light will be distributed in larger region along the laser cavity, that is to say, light field will be flattened and spatial hole burning can be suppressed in such flexible structure. Based on the ESDC structure, different sampling structures in a DFB laser array can also be obtained by stepping the sampling periods; therefore, multi-wavelength laser array can be designed and fabricated, which would simplify the fabrication process, and may be more suitable for the high precision and massive fabrication of DFB laser and laser array with reduced spatial hole burning. Highlights: We proposed an equivalent-stepped-duty cycle (ESDC) grating structure. The ESDC profile is realized by stepping the duty cycle of a Sampled Bragg grating. An equivalent-stepped-index-coupled (ESIC) DFB laser is based on the ESDC grating. The SHB is suppressed effectively in the ESIC DFB laser. The ESIC DFB laser array can be designed and fabricated easily based on the REC.